STUDI KASUS BEBAN KERJA DENGAN METODE FULL TIME EQUIVALENT DALAM MEMPRODUKSI KOMPONEN BENCH VISE 125 - Arifin, Rifi Wijayanti Dual; Ariyani, Emma Dwi; Muhammad, Achmad; Sadikin, Supriyadi; Ariawati, Mutiara Septina (LPPM STIE Muhammadiah Bandung, 2025)
Productivity in the manufacturing industry is greatly influenced by the physical capacity of workers, especially in jobs involving heavy physical activity, which can cause fatigue and reduce efficiency. One way to increase efficiency is to eliminate waste in production, such as waiting time and product defects, which can be reduced with the Lean Manufacturing approach through continuous improvement. This study aims to analyze the workload of operators in the bench vise 125 production process in the Polytechnic X production laboratory by applying the Full Time Equivalent (FTE) method to determine the optimal number of workers where the calculation results show that three of the four processes have excess loads that can be anticipated by adding seven operators to each process. The results of this study are expected to be information and considerations as well as evaluation discussions in one of the bases for determining policies in the Polytechnic X production laboratory.